Utility of the wireless motility capsule and lactulose breath testing in the evaluation of patients with Parkinson's disease who present with functional gastrointestinal symptoms. Issue 1 (1st February 2017) - Su, Andrew; Gandhy, Rita; Barlow, Carrolee; Triadafilopoulos, George
Abstract : Background: The aetiology and origin of gastrointestinal symptoms in Parkinson's disease (PD) remains poorly understood. Gastroparesis, small bowel transit delay and bacterial overgrowth may, individually or collectively, play a role. Aims: In patients with PD and functional gastrointestinal symptoms, we aimed to determine the utility of the wireless motility capsule and lactulose breath tests in further defining their symptoms' aetiology. Methods: In this retrospective cohort study, consecutive patients with PD and functional gastrointestinal symptoms underwent clinical assessment, as well as wireless motility capsule and lactulose breath testing using standard protocols. Results: We studied 65 patients with PD and various gastrointestinal symptoms. 35% exhibited gastroparesis by the wireless motility capsule study, 20% small bowel transit delay, while 8% had combined transit abnormalities, suggestive of overlapping gastric and small bowel dysmotility. Small bowel bacterial overgrowth was seen in 34% of cases. Symptoms of abdominal pain, regurgitation, bloating, nausea, vomiting, belching and weight loss could not distinguish between patients with or without gastroparesis, although bloating was significantly more prominent (p<0.001) overall and specifically more so in patients with slow small bowel transit (p<0.01). There was no relationship between delayed small bowel transit time and bacterial overgrowth (p=0.5); PD scores and duration were not correlated with either the transit findings or small bowel bacterial overgrowth. Conclusions: Functional gastrointestinal symptoms in patients with PD may reflect gastroparesis, small bowel transit delay or both, suggesting motor and/or autonomic dysfunction, and may be associated with small bowel bacterial overgrowth. The wireless motility capsule and lactulose breath testing are non-invasive and useful in the assessment of these patients.